Prevalence of Mia antigen and anti-Mia antibody among patients from a university hospital in Malaysia (Bangladesh Journal of Medical Science, 2025)
Background Mia is a low-frequency red cell antigen associated with the MNS glycophorin variants, commonly found in individuals with the GP. Mur phenotype in Southeast Asia. The alloantibody, anti-Mia, is linked to hemolytic transfusion reactions and hemolytic disease of the fetus and newborn. This study aimed to assess the prevalence of Mia antigen expression and the presence of anti-Mia antibodies. Methods This study was conducted at the Blood Bank unit of Universiti Kebangsaan Malaysia Medical Centre. The Mia antigen phenotyping was performed from June 2018 to September 2019 using random sampling of blood samples collected for pre-transfusion testing and analyzed using a monoclonal anti-Mia antibody. The prevalence of anti-Mia antibodies was evaluated from samples sent for antibody screening and identification over one year from October 2018 to September 2019. Results A total of 694 patients participated in the Mia antigen study, including 347 Malays, 233 Chinese, and 114 Indians. The overall prevalence of the Mia antigen was 18 out of 694 (2.6%). The highest frequency was observed in the Chinese group (4.7%), followed by Malays (1.7%) and Indians (0.9%), with statistical significance (p=0.038). For anti-Mia antibody study, 13,011 samples were screened for antibodies, resulting in 231 alloantibody positive cases (1.8%), with anti-Mia antibodies detected in 61 cases, reflecting a prevalence of 0.5%. Conclusion: Given Malaysia’s diverse ethnic makeup, understanding Mia antigen frequency is essential. This study reveals a relatively low prevalence of the Mia antigen alongside a notable incidence of anti-Mia antibodies compared to neighboring countries.Bangladesh Journal of Medical Science Vol. 24 No. 02 April’25 Page : 621-628